Political Dynasty Representation in The 2024 Presidential and Vice Presidential Election Candidates in Kompas Daily Editorial Cartoons - Prabowo, Antonius Sulistyo; Murtiningsih, Bertha Sri Eko; Priyonggo, Ambang (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Political dynasties have emerged as a significant concern in Indonesian politics, particularly in the context of the 2024 presidential election. This study aims to analyze the representation of political dynasties in editorial cartoons published by the Kompas daily newspaper during the 2024 Presidential Election period. Using a descriptive qualitative approach with Roland Barthes' semiotic analysis, this study examines four editorial cartoons published between October 19, 2023, and February 10, 2024, focusing on their denotative, connotative, and mythical meanings. The results show that the cartoons represent power and dominance through the manipulation of visual size, contain criticism of the political system through various symbols such as tornadoes and the Constitutional Court building wrapped in an octopus, and depict society through various crowd expressions that reflect Indonesian pluralism. The research findings identify three main myths: the myth of power and political elites that reflects the Javanese cultural concept of centralized authority; myths related to money politics that represent the influence of economic power; and the myth of democracy without people that highlights low party identification among voters. This study demonstrates how editorial cartoons use symbolism, exaggeration, distortion, stereotypes, caricatures, and humor to deliver sharp political criticism. This research contributes to understanding how editorial cartoons function as an effective medium for social criticism by visually representing important issues in the Indonesian democratic process, inviting readers to reflect on the challenges of democracy while encouraging improvements toward a more substantive political system.